Pengetahuan Bidan Mempengaruhi Praktik Bidan dalam Konseling Pemeriksaan IVA pada Wanita Usia Subur - Siti Rochwati; Sutopo Patria Jati; Antono Suryoputro (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTPeer Midwive Knowledge Influencing Practice in Counseling About Examination Visual Inspection Of Acetic Acid On Couple Women Of Childbearing Age; Cervical cancer is becoming a disease number two killer of women in Indonesia, after breast cancer, it is due to 95% of HPV virus (Human Papiloma Virus). HPV infection went unnoticed until the disease reaches an advanced stage. If cancer is found at an early stage can be cured completely with the method IVA (Visual Inspection Acetic Acid) easier, screening can be performed with a wider scope. Cervical cancer cases in the Kendal district was increased in 2009 (3,31%), in 2010 (3,77%), in 2011 (4,45%), while decreasing IVA inspection visit in 2010 (4,34%), 2011 (4,33%), 2012 (3,96%). Therefore midwife in addition to providing health services can also provide counseling realization of behavior IVA test inspection. The purpose of this research is to analyzed the relationship of knowledge midwives with practice in counseling about examination visual inspection of acetic acid on couple women of childbearing age. Methods and design research is quantitative descriptive explanatory with correlative and cross sectional approach, using sampling saturated with 60 respondents by midwife that have trained in the Kendal district. The results from 9 variables majority age ≥41 years =66,7%, educatin majority of DI and D III =78,3%, the majority of the working time ≥10 years = 95%, approximately 55% majority of the knowledge and counseling practice the majority 73,3%. Chi square test shows that the relationship between knowledge with practice in counseling about examination visual inspection of acetic acid on couple women of childbearing age p value 0,000. Midwives is expected to increase their knowledge, so that it can perform well counseled about IVA to couples of reproductive age want to do test IVA.Keywords: Midwives, Knowledge, Counseling Practice, IVA.